2002
DOI: 10.1128/aem.68.3.1319-1324.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Campylobacter jejuni and Campylobacter coli in Environmental Waters by PCR Enzyme-Linked Immunosorbent Assay

Abstract: A PCR enzyme-linked immunosorbent assay (ELISA) assay was applied to the detection of Campylobacter jejuni and Campylobacter coli in environmental water samples after enrichment culture. Bacterial cells were concentrated from 69 environmental water samples by using filtration, and the filtrates were cultured in Campylobacter blood-free broth. After enrichment culture, DNA was extracted from the samples by using a rapid-boiling method, and the DNA extracts were used as a template in a PCR ELISA assay. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The false negatives may be due to differences in sensitivity of the two methods, PCR-ELISA (Ն10 2 CFU/ml) and culture (1 CFU/ml) (34). This difference in the sensitivity between PCR and culture may be due in part to volume constraints, since the sample volumes that can be processed by culture methods are larger than those for PCR (milliliters versus microliters) (32,34,48). However, an enrichment step could circumvent this problem by bringing salmonella cell numbers into the detection range of PCR-ELISA (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The false negatives may be due to differences in sensitivity of the two methods, PCR-ELISA (Ն10 2 CFU/ml) and culture (1 CFU/ml) (34). This difference in the sensitivity between PCR and culture may be due in part to volume constraints, since the sample volumes that can be processed by culture methods are larger than those for PCR (milliliters versus microliters) (32,34,48). However, an enrichment step could circumvent this problem by bringing salmonella cell numbers into the detection range of PCR-ELISA (34).…”
Section: Discussionmentioning
confidence: 99%
“…Salis et al indicated that their PCR-ELISA could detect one Campylobacter cell per reaction but only with purified DNA template (46). PCR-ELISA has been applied toward the detection of Campylobacter species from poultry (41), clinical samples (32), and environmental waters (48), but few studies have evaluated the utility of PCR-ELISA for detecting Campylobacter directly from samples. Lawson et al reported using PCR-ELISA to detect Campylobacter directly from fecal samples (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of C. coli in samples of environmental water has been reported previously (33,39), and there have been a small number of reports linking cases of human disease to water supplies (11,21). It has also been reported that a laboratory strain of C. coli is less well adapted to survival in water than C. jejuni or C. lari is (37).…”
Section: Vol 70 2004 Characteristics Of C Coli From Cheshire Studymentioning
confidence: 95%
“…Other reported sources of infection include contaminated water and raw milk (22,32); however, in most cases the exact source of disease is not determined (43). Environmental loading and transmission may be factors associated with nonoutbreak cases, particularly those related to contamination of ambient waters (4,28,41,42).…”
mentioning
confidence: 99%